The Implementation of Creative Learning Models in Teaching Writing in Junior High School - Kurniasih, Esti; Hartanti, Lina Purwaning (New Language Dimensions, 2020)
Creative learning is a learning process that requires teachers to motivate and bring up the students creativity, both in the context of creative thinking and in the context of creative in doing things during the learning process, using a variety of learning methods and strategies, such as group work, problem solving, and so on. In line with creative learning, this study further aims to describe the development of learning devices (i.e. RPP) and the implementation of learning activities that use creative learning models in teaching writing skill in Junior high School. Based on the results of data analysis, it can be concluded that most of the RPPs developed had included all the components of RPP in detail, start from school identity to the assessment. While related to the implementation of learning activities that use creative learning models in teaching writing, it can be concluded that the implementation had applied creative learning models in three learning activities, they are pre, whilst, and post activities.